Influence of intraoperative conventional fluoroscopy versus cone beam CT on long-term clinical outcome in isolated displaced talar fractures - Vetter, Sven Y.; Swartman, Benedict; Schnetzke, Marc; Keil, Holger; Franke, Jochen; Grützner, Paul Alfred; Beisemann, Nils (Journal of orthopaedic surgery and research, 2019)
The objective of the study was to compare the radiologic and clinical outcome of patients with an isolated displaced talus fracture treated intra-operatively with either conventional fluoroscopy or additional cone beam computed tomography (CT).